Sexually transmitted infections in indigenous populationsin Brazil – reviewand literature review - Carvalho, Newton Sérgio de (2011)
Sexually transmitted diseases, including HIV infection (STD/HIV) among the indigenous populations are not very well known or reported in Brazil. Through a number of specific studies in some villages we obtain a broad view of the panorama which might be occurring within these communities. It is possible to observe the advantage in favor of the people from the Amazon for holding the largest number of ethnic groups, the largest population and greatest preservation of culture. It can also be noted that studies in this area are more anthropological than linked to health care, showing that the preservation of the cultural aspect is considered a priority in relation to the illnesses.